Data Sharing Statements for Clinical Trials: A Requirement of the International Committee of Medical Journal Editors. - Darren B Taichman; Peush Sahni; Anja Pinborg; Larry Peiperl; Christine Laine; Astrid James; Sung-Tae Hong; Abraham Haileamlak; Laragh Gollogly; Fiona Godlee; Frank A Frizelle; Fernando Florenzano; et al. (PLoS Medicine)
The International Committee of Medical Journal Editors announces requirements that a data sharing plan be prospectively registered, and a data sharing statement be included in submitted manuscripts, for clinical trials to be published in ICMJE journals.